2020
DOI: 10.3390/microorganisms8091291
|View full text |Cite
|
Sign up to set email alerts
|

Mining the Microbiome of Key Species from African Savanna Woodlands: Potential for Soil Health Improvement and Plant Growth Promotion

Abstract: (1) Aims: Assessing bacterial diversity and plant-growth-promoting functions in the rhizosphere of the native African trees Colophospermum mopane and Combretum apiculatum in three landscapes of the Limpopo National Park (Mozambique), subjected to two fire regimes. (2) Methods: Bacterial communities were identified through Illumina Miseq sequencing of the 16S rRNA gene amplicons, followed by culture dependent methods to isolate plant growth-promoting bacteria (PGPB). Plant growth-promoting traits of the cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 110 publications
(128 reference statements)
1
17
2
Order By: Relevance
“…Altogether, these results have shown that the bacterial diversity in the Miombo rhizosphere is highly diverse, and apparently more conserved within oxi-soils (O). These contrast with a similar study performed in another important savanna ecosystem, the Mopane woodlands [ 9 ], where the rhizobacteria were found to be less abundant (700–800 OTUs vs ca. 1000–1200) and less diverse (Shannon H index ca.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Altogether, these results have shown that the bacterial diversity in the Miombo rhizosphere is highly diverse, and apparently more conserved within oxi-soils (O). These contrast with a similar study performed in another important savanna ecosystem, the Mopane woodlands [ 9 ], where the rhizobacteria were found to be less abundant (700–800 OTUs vs ca. 1000–1200) and less diverse (Shannon H index ca.…”
Section: Resultscontrasting
confidence: 99%
“…4 vs ca. 7–8) than the results found here [ 9 ]. The results also contrasted with those observed in the subtropical Laurisilva forest, where fire drastically reduced bacterial abundance (from ca.…”
Section: Resultssupporting
confidence: 46%
See 3 more Smart Citations